Pendampingan Pendidikan Anak di Kelurahan Genteng Surabaya - Achmad Hidayatullah (Universitas Muhammadiyah Surabaya, 2017)
Child problems arise in various areas, such as child abuse, child sexual abuse, frees sex, drugs etc. Therefore, this dedication will focus on children's problems, especially in the context of education. This devotion activity was conducted for 30 days in RW III tile village. As for the service in the form of parenting and child training or parenting, reinforcement and mentoring of children learning and play park which is held in RW hall, and also assistance to youth organization of karang taruna village to empower children and rema in RW III tile village. Assistance to the children's learning park involves collaborating with parents and youth. By giving counseling and parenting to parents, the expectation of parents have more time to spare and control children, while involvement of cooperation with youth to empower teenagers to participate actively to build character and village education.